Educational and socioeconomic status of Majhis: A study of Adamtar, Dhading district of Nepal - Som Nepali (EDUCATIO : Journal of Education, 2022)
The research was conducted to find the educational status of Majhis. This is solely descriptive research in which educational condition of Majhis has been described along with their social and economic condition. Majhis should have improved their educational, social and economic condition because of easy access of school, market and social and political exposure. However there are no significant changes in their life style. So, the research was carried out. Data for this research were collected through interview and household survey. It was education issues. Therefore data were taken from students, teachers and head of the family.